PUTUSAN PAILIT ATAS PERUSAHAAN ASURANSI DAN AKIBAT HUKUMNYA DI INDONESIA - Annisa Chaula Rahayu, Herman Susetyo*, Paramita Prananingtyas (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Bankruptcy is a general sequestration of the assets of the debtor are no longer able to pay its debts have matured and can be billed in accordance with Article 2 paragraph (1) of Law No. 37 Year 2004 on Bankruptcy and Suspension of Payment. The bankruptcy of the insurance company ever in Indonesia, which brings the impact of changes to the Law. 4 Year 1998 on the bankruptcy of the Bankruptcy Insurance Company Manulife Indonesia terminated by Decision No. 10/PAILIT/2002/PN.NIAGA.JKT.PST were subsequently canceled by the Supreme Court No.. 021/K/N/2002. Based on these results it can be concluded that the bankruptcy procedure against PT. Life Insurance Manulife Indonesia is not in accordance with Law no. 4 of 1998 on Bankruptcy in particular Article 67 paragraph (5) and Article 70, and not in accordance with the provisions contained in Article 20 paragraph (1) of Law no. 2 of 1992 about Insurance Business which has the authority to request the court to be bankrupt insurance company on the grounds of public interest is the Minister of Finance. The existence of the bankruptcy case against PT. Life Insurance Manulife Indonesia legal consequences that birth Law. 37 Year 2004 on Bankruptcy and Suspension of Payment this is because the Law no. 4 of 1998 on Bankruptcy masaih there are many disadvantages and yet accommodate the authority of the Minister of Finance to issue liquidation of insurance company.